(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2023)
the aim of the study is to reveal the underlying factors from variable data collected on the results of the web-based ideas management systems related to management and tangible results in companies. The purpose of the factor analysis process is to collect the information contained in a large number of changes in such a way as to obtain latent factors with minimal data loss. Authors have conducted global survey for enterprises that apply these systems (n>500). The 8 variables that fit together reveal the latent factor “tangible” or tangible results and the remaining 6 variables that together reveal the latent factor “managerial” or the management results.